Sometimes a Colonnade is Just a Porch - Thomas L. Schumacher (Oz, 2000)
The history of modern architecture in the twentieth century, and into the twenty-first, is periodically concerned with the questions: who is Modern, what is Modern, what is Modern enough, and what does Modern mean in social and political terms? In a practical sense, the ideological battles between the “Moderns” and the “Ancients” over the past century have resembled the politics of a banana republic.